INTERAKSI EDUKATIF DALAM PEMBELAJARAN PAI UNTUK MENINGKATKAN KUALITAS BELAJAR DI SMAN 1 JARO KECAMATAN JARO KABUPATEN TABALONG - Hatmiah Hatmiah (ADISAM PUBLISHER, 2023)
The educator acts as a guide. Therefore, educators must try to liven up the atmosphere and provide motivation so that good interaction occurs (educational interaction). Educative interaction in the learning process between educators and students greatly influences what is learned can be responded well by students. Based on this statement, the problem in this study can be formulated, namely how is the educational interaction in PAI learning to improve the quality of learning at SMAN 1 Jaro, Jaro District, Tabalong Regency? The purpose of this research is to find out educational interactions in PAI learning to improve the quality of learning at SMAN 1 Jaro, Jaro District, Tabalong Regency. The subjects in this study were PAI teachers and students at SMAN 1 Jaro, Jaro District, Tabalong Regency. While the object in this study is educational interaction in PAI learning to improve the quality of learning at SMAN 1 Jaro, Jaro District, Tabalong Regency. Data collection techniques are carried out by means of observation, interviews, and documentation. Data analysis techniques use qualitative and provide conclusions using general methods based on existing data in the field. The results of this study indicate that educative interaction in PAI learning to improve the quality of learning at SMAN 1 Jaro, Jaro District, Tabalong Regency, includes: 1) A one-way educational interaction pattern has been implemented. In this interaction, the PAI teacher explained the PAI material using the lecture method and the story method. 2) The pattern of two-way educational interaction has been implemented. In this interaction, the PAI teacher really explained the PAI material using the question and answer method. 3) Multi-directional educational interaction patterns have been implemented. In this interaction, the PAI teacher really explained the PAI material using the discussion method and group method, as well as the question and answer method.